2009
DOI: 10.1097/hjr.0b013e32831c1383
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor profiles and use of cardiovascular drug prevention in women and men with peripheral arterial disease

Abstract: The patients' risk factor profiles differed among the PAD stages. Smoking duration already seemed to be a risk factor for women with PAD after 10 years of smoking, as compared with 30 years for men, and fewer women reported use of preventive medication. These observations may partly explain the sex differences in prevalence that were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Eight studies (14.5%) recruited only men,32 39 51 56 58 60 71 72 2 (3.6%) only women,53 54 and 45 (81.8%) both 21–31 33–38 40–50 52 55 57 59 61–70 73–75. Forty-three (78.2%) were cross-sectional studies,22–26 28–31 33 34 36 40–45 47–50 52–55 57–71 74 75 10 (18.2%) were cohort studies21 27 32 38 39 46 51 56 72 73 and 2 (3.6%) were case-control studies 35 37. Forty-seven (84.5%) studies defined PAD using the ABI,21–26 29–34 36–38 40–49 52–55 57–71 73–75 and 7 (12.7%) based on symptoms of intermittent claudication, using either the Edinburgh, WHO/Rose or San Diego claudication questionnaires 28 35 39 50 51 56 72.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies (14.5%) recruited only men,32 39 51 56 58 60 71 72 2 (3.6%) only women,53 54 and 45 (81.8%) both 21–31 33–38 40–50 52 55 57 59 61–70 73–75. Forty-three (78.2%) were cross-sectional studies,22–26 28–31 33 34 36 40–45 47–50 52–55 57–71 74 75 10 (18.2%) were cohort studies21 27 32 38 39 46 51 56 72 73 and 2 (3.6%) were case-control studies 35 37. Forty-seven (84.5%) studies defined PAD using the ABI,21–26 29–34 36–38 40–49 52–55 57–71 73–75 and 7 (12.7%) based on symptoms of intermittent claudication, using either the Edinburgh, WHO/Rose or San Diego claudication questionnaires 28 35 39 50 51 56 72.…”
Section: Resultsmentioning
confidence: 99%
“…Current smokers were compared with never smokers in 29 (52.7%) studies,21 23–25 27–29 31 32 37 40 42–44 46 50–53 56 58 60 62 66 67 71–73 75 and with non-smokers (never plus ex-smokers) in 19 (34.5%) studies 22 26 30 33–36 38 45 47 48 55 57 63 65 67–69 74. Seven studies (three cross-sectional,36 58 71 three cohort,51 56 72 and one case-control37) reported evidence of a dose-relationship with the amount smoked or duration of smoking.…”
Section: Resultsmentioning
confidence: 99%
“…Women with this diagnosis were much less likely to receive any of the recommended medications for their condition (ASA, ACE inhibitors and/or angiotensin receptor blockers or lipid lowering medications) compared to men. These observed prescribing practices are also supported by a study in Swedish primary care facilities, which shows that men with PVD have higher odds of being prescribed a lipid-lowering therapy (OR = 1.3; 95% CI: 1.1-1.5), ACE inhibitors or beta blockers (OR = 1.3; 95% CI: 1.0-1.7), or antiplatelet therapy (OR = 1.5; 95% CI: 1.2-1.9) than women [15]. These trends are also reflected by much earlier research (circa the late 1980′s), which documented the age-adjusted likelihood of having a procedure related to PVD as being 1.7 times higher in men than women [16].…”
Section: Discussionmentioning
confidence: 97%
“…Despite several sets of guidelines providing physicians with recommendations regarding best medical management, systemic vascular events are probably not optimally treated in this group of patients. [6][7][8] Current recommendations include antiplatelet therapy for any PAD patient (class I level) and ondemand treatment of statins and antihypertensive drugs to achieve the target values for serum lipids and blood pressure. [9][10][11][12] The recommendations are, however, largely based on data derived from subgroup analyses of trials performed in populations with manifestations in other vascular territories.…”
mentioning
confidence: 99%